Cortical-Subcortical Interactions in Depression: From Animal Models to Human Psychopathology - Heller, Aaron S. (Frontiers in Systems Neuroscience, 2016)
Depression is a debilitating disorder causing significant societal and personal suffering. Improvements in identification of Major Depressive Disorder (MDD) and its treatment are essential to reduce its toll. Recent developments in rodent models of MDD and neuroimaging of humans suffering from the disorder provide avenues through which gains can be made towards reducing its burden. In this review, new findings, integrating across rodent models and human imaging are highlighted that have yielded new insights towards a basic understanding of the disorder. In particular, this review focuses on cortical-subcortical interactions underlying the pathophysiology of MDD. In particular, evidence is accruing that dysfunction in prefrontal-subcortical circuits including the amygdala, ventral striatum, hippocampus and dorsal raphe nucleus are associated with MDD status.